Effect of milling time on magnetite (Fe3O4) crystal structure made from volcanic minerals from Mount Talang, West Sumatra - Yuli Pratiwi; Ramli Ramli; Ratnawulan Ratnawulan (PILLAR OF PHYSICS, 2017)
The available of iron sands in west sumatera only exploit in raw condition (raw material) so that the value of sell is low. One of solution to make higher value of sell is knowing it’s characteristic. Iron sands characteristic can be known based on crystal structure, the size of crystal and magnetite structure from iron sands around Kecamatan Lembah Jaya, Kecamatan Gunung Talang and Kecamatan Danau Kembar, Kabupaten Solok, Provinsi Sumatera Barat as the resut of milling time variation. This research aim are to investigate the influence of milling time to magnetite crystal and  investigate the influence of milling time to size of magnetite crystal using X-Ray Diffraction. This is experiment research that have been done in Material Laboratory of Physics Departement. In this research, there is a variation of time milling. X-Ray Diffraction (XRD) is used in identification of structure dan size of crystal. X-Ray Flouresence (XRF) is used in gather the data of magnetite level in iron sands before and after milling. The result of this research shows that increasing time milling caused the change of fasa from hematite to magnetite. Increasing time milling variation cause the change of magnetite structure from rhombohedral to cubic structure. Increasing the time milling cause size of magnetite crystal increase up to  certain time milling and then decrease, then some keep increase again. Such as a magnetite crystal before milling, 88,01 nm and after milling in 25 hours it becomes 71,10 nm, milling in 30 hours it becomes 78,63 nm. In 35 and 40 hours of milling, it decreases to 55,42 and 49,86 nm. In 45 hurs milling, it increases to 66,25. The smaller the size of crystal, the magnetite particle can be used as heavy metal binding that present in waste